Virtual Try-On Systems in Fashion Consumption: A Systematic Review - Caixia Chen; Jiayan Ni; Peishan Zhang (Applied Sciences)
The application of virtual try-on (VTO) technologies in the fashion industry is garnering increasing attention and is regarded as a significant innovation in enhancing the consumer experience for fashion shoppers. This study conducts a systematic review to evaluate the impact of VTO systems on consumer behavior and experiences within the fashion industry. By analyzing 69 research articles, we identified key factors influencing consumers’ purchasing decisions and VTO adoption intentions. These factors include attitudes, media, symbolic gratification, technological gratification, emotional values, utilitarian values, and user attributes. Based on these findings, we construct conceptual frameworks that clearly delineate how direct factors and their influencing elements impact consumers’ purchase and technology adoption behaviors. This review synthesizes the psychological and technological dimensions shaping consumer behavior, addressing critical gaps in the literature specific to fashion consumption. Moreover, future research directions were discussed. By addressing key challenges such as boundary factors, user segmentation, and technological advancements, this study offers actionable insights to guide researchers and practitioners in creating more personalized, immersive, and effective VTO systems in the fashion industry.